Pengaruh Premenstrual Syndrome Terhadap Job Performance Melalui Negative Affect Dengan Perceived Organizational Support Sebagai Variabel Moderasi - Herlina Herlina; Meiske Claudia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study analyzes the effect of Premenstrual Syndrome (PMS) on Job Performance through Negative Affect with Perceived Organizational Support (POS) as a moderating variable among 78 female civil servants at the Regional Secretariat of Tanah Bumbu Regency. Primary data were collected using questionnaires and analyzed with PLS-SEM. The findings indicate that PMS negatively affects job performance and positively affects negative affect. Negative affect decreases job performance, while POS improves job performance and weakens the negative effect of negative affect on job performance.